2015
DOI: 10.3747/co.22.2661
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Localized Esophageal and Gastroesophageal Junction Cancer in Older Patients

Abstract: Background Older patients are commonly excluded from clinical trials in esophageal and gastroesophageal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Several authors investigated the accessibility of EP to different treatment options [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Among EP with curable disease, only 50–69% seemed to receive treatment with curative intent [ 12 , 13 , 15 , 16 ]. Münch et al even report that for similar tumor stages with YP, 25% of EP received palliative and not curative treatment [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors investigated the accessibility of EP to different treatment options [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Among EP with curable disease, only 50–69% seemed to receive treatment with curative intent [ 12 , 13 , 15 , 16 ]. Münch et al even report that for similar tumor stages with YP, 25% of EP received palliative and not curative treatment [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Münch et al even report that for similar tumor stages with YP, 25% of EP received palliative and not curative treatment [ 19 ]. The most frequently used modality was definitive chemoradiation (DCRT) in 37–64% of EP [ 12 , 13 , 14 ], while only 7–36% of them were offered surgery [ 12 , 13 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The results of a phase II, single-arm study evaluating platinum-based chemotherapy combined with radiotherapy in patients older than 75 years with esophageal carcinoma suggested that chemotherapy is feasible and tolerable in elderly patients. 14 Meanwhile, there have been several retrospective studies [14][15][16][17][18][19][20][21][22][23][24] in elderly patients with OC had indicated that concurrent chemoradiation might be an optimal strategy for elderly patients with OC. Studies with more than 20 patients were listed in Table 6.…”
Section: Discussionmentioning
confidence: 99%